Role of PACAP in Female Fertility and Reproduction at Gonadal Level – Recent Advances - Reglodi, Dora; Tamas, Andrea; Koppan, Miklos; Szogyi, Donat; Welke, Laura (Frontiers in Endocrinology, 2012)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a pleiotropic neuropeptide, first isolated from hypothalamic extracts, but later shown in peripheral organs, such as endocrine glands, gastrointestinal system, cardiovascular system and reproductive organs. PACAP plays a role in fertility and reproduction. Numerous studies report on the gonadal regulatory effects of PACAP at hypothalamo-hypophyseal levels. However, the local effects of PACAP at gonadal levels are also important. The present review summarizes the effects of PACAP in the ovary. PACAP and its receptors are present in the ovary, and PACAP plays a role in germ cell migration, meiotic division, follicular development and atresia. The autocrine-paracrine hormonal effects seem to play a regulatory role in ovulation, luteinization and follicular atrophy. Altogether, PACAP belongs to the ovarian regulatory peptides.